(untitled) (Scientia Agropecuaria, 2023)
The objective of this research was to evaluate the effects of dynamic high pressure at different processing temperatures, on the extraction of bioactive compounds from Peruvian purple corn cob. The purple corn cobs were ground and sieved to then be mixed with an acidified 20% ethanol-water solution (pH 2) in a 1:30 (w/v) ratio. The hydroalcoholic extracts were subjected to maceration and high dynamic pressure processes varying temperature (25 °C to 60 °C) and pressure (0.01 MPa - 60 MPa), and the bioactive compounds content and antioxidant activity were evaluated. The results showed that dynamic high pressure at 60 MPa / 45 °C was capable of obtaining extracts with bioactive compound contents and high antioxidant activity corresponding to those obtained using the conventional process of 2.5 hours / 65 °C. Seven different anthocyanins were identified by liquid chromatography in the extracts obtained by the dynamic high pressure, mainly cyanidin-3-glucoside, pelargonidin-3-glucoside and peonidin-3-glucoside, and their respective malonyl derivatives. The dynamic high pressure increased the extraction of anthocyanins by more than 108% and obtained them in one step, thus appearing as a new alternative, eco-friendly method for the extraction of bioactive compounds from plant tissues.